2020
DOI: 10.21203/rs.3.rs-26662/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An outbreak of intestinal schistosomiasis, alongside increasing urogenital schistosomiasis prevalence, in primary school children on the shoreline of Lake Malawi, Mangochi District, Malawi

Abstract: Background: Intestinal schistosomiasis was not considered endemic in Lake Malawi until November 2017 when populations of Biomphalaria pfeifferi were first reported; in May 2018, emergence of intestinal schistosomiasis was confirmed. This emergence was in spite of ongoing control of urogenital schistosomiasis by preventive chemotherapy. Our current study sought to ascertain whether intestinal schistosomiasis is transitioning from emergence to outbreak, to judge if stepped-up control interventions are needed.Met… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…This is the first study in Malawi to estimate the prevalence of S. mansoni infection in adults with NCDs. There was high prevalence of S. mansoni infection in this population which is consistent with estimates in school going children in the district of 10 – 56.7% (12). This is also consistent reports of an epidemic of both S. mansoni and S. haematobium in the district.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is the first study in Malawi to estimate the prevalence of S. mansoni infection in adults with NCDs. There was high prevalence of S. mansoni infection in this population which is consistent with estimates in school going children in the district of 10 – 56.7% (12). This is also consistent reports of an epidemic of both S. mansoni and S. haematobium in the district.…”
Section: Discussionsupporting
confidence: 89%
“…It has an NCD clinic that operates twice a week on Tuesdays (diabetes clinic) and Thursdays (hypertension clinic). Recent studies in Mangochi district have demonstrated an emerging epidemic of S. mansoni infection amid the increasing prevalence of S. haematobium infections in this setting (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cessation of the COUNTDOWN project may have played a role. Strategies recommended by Kayuni et al 42 for investigating community outbreaks of intestinal schistosomiasis might be useful for identifying the factors responsible for the rapid emergence of S. mansoni in this area.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the high coverage rates obtained in the study districts over the two years there is only slow progress towards achievement of the goal to reduce burden of schistosomiasis and STH to levels of no public health importance in Malawi by 2025. Recent prevalence studies done across Malawi after introduction of MDA in 2012, including in the study districts have pointed to persistent infections [6, [13][14][15][16][17][37][38][39][40][41][42] and reinfections [37][38][39][40][41][42] occurring within a year despite sustained annual MDA campaigns implemented throughout the country. These persistent infections and reinfections are similar to those observed in other studies carried out in Cote d'Ivoire, Kenya, Mozambique, Tanzania [43] and Togo [44].…”
Section: Community Participation In Mda Deliverymentioning
confidence: 99%